Islamization of Knowledge During the Caliphate of Harun Al-Rashid: A Historical Analysis - Evalinda Evalinda; Daud Rasyid; Abdullah Ghulam Nazih; Intan Wulansari; Hayatuddin Hayatuddin (Journal of Noesantara Islamic Studies, 2025)
This study examines the process of the Islamization of knowledge during the reign of Caliph Harun al-Rashid as a significant phase in the development of Islamic civilization. During this period, the Islamic world absorbed foreign knowledge from Greek, Persian, Indian, and Roman traditions, which was subsequently translated, critically evaluated, and integrated into the Islamic epistemological framework. Employing a qualitative method with a literature-based approach, this research analyzes classical historical sources and contemporary scholarly journals using historical-descriptive analysis. The findings indicate that Bayt al-Hikmah functioned as a major center for translation and scientific development, fostering cross-cultural and interreligious scholarly collaboration and contributing to advances in mathematics, medicine, astronomy, and chemistry. The integration of external knowledge also influenced the development of logic, kalam, and usul al-fiqh, leading to a more rational intellectual tradition. Despite criticism from traditionalist groups, particularly concerning the influence of Greek philosophy, this process strengthened Islamic epistemological boundaries and ensured that scientific development remained aligned with the principle of tawhid.